New advancements in conventional and DES-based extraction of phenolic compounds from Aglianico red grape pomace - Errichiello Francesco; Joana Azevedo; Boris Basile; Victor De Freitas; Martino Forino; Alessandro Mataffo; Joana Oliveira; Susana Soares (OENO One)
Grape pomace is the most abundant winery solid waste, accounting for about 60%. Still, it is an unvaluable source of bioactive molecules that can be recovered and reused in the frame of circular economy. In this study Deep Eutectic Solvents (DES) obtained with choline chloride and organic acids by far outperformed conventional solvents (methanol and acetone). In particular, choline chloride:oxalic acid (1:1 at 40°C) emerged as the best one affording a total phenolic content of 43.0 mg/g (dry weight). By means of LC-MS/MS analysis, specific phenols were identified and quantified including anthocyanins, flavan-3-ols, flavonols, phenolic acids and stilbenes. DES extracts also exhibited superior DPPH-based antioxidant activity than conventional ones. These results demonstrated the efficacy of DES in recovering phenolics. The adoption of green solvents for treating waste biomass can significantly benefit wineries and other food industries by increasing their sustainability and diversifying their profits in the frame of circular economy.